Mechanical properties study of pseudo-stem banana fiber reinforced epoxy composite - Maleque, M. A.; Belal, F. Y; Sapuan, S. M. (KING FAHD UNIV PETROLEUM MINERALS, 2007)
Mechanical properties study of pseudo-stem banana fiber reinforced epoxy composite